VIGIAR A ORTODOXIA: LIMITES E COMPLEMENTARIDADES ENTRE A JUSTIÇA ECLESIÁSTICA E A INQUISIÇÃO NA AMÉRICA PORTUGUESA - Muniz, Pollyanna Gouveia Mendonça; Mattos, Yllan De [UNESP] (Universidade de São Paulo, 2014)
This article aims to contribute to a better knowledge of ecclesiastical and inquisitorial structures in the Portuguese world, especially in the America. The focus of this research is to understand the relationship between the ecclesiastical and inquisitorial tribunals, with a view to demonstrating some aspects of collaboration in many different places and times, in addition to its peculiarities. For this, we analyze their Regiments and put them in relation with the different cases and processes in order to perceive the harder the idiosyncrasies of each Court.

Este artigo tem como objetivo contribuir para o melhor conhecimento das estruturas eclesiásticas e inquisitoriais no mundo português, sobretudo na América. O foco dessa investigação é perceber a relação estabelecida entre os tribunais eclesiástico e inquisitorial, com o fito de demonstrar alguns aspectos dessa colaboração nos mais diferentes lugares e tempos, além de suas particularidades. Para isso, analisamos seus regimentos e os colocamos em relação com os diferentes casos e processos a fim de perceber com mais afinco as idiossincrasias de cada tribunal.
WATCH ORTHODOXY: LIMITATIONS AND COMPLEMENTARITIES BETWEEN THEINQUISITION AND ECCLESIASTICAL JUSTICE IN PORTUGUESE AMERICA
Keywords: Inquisition; Ecclesiastical Justice; Church; Colonial Brazil; Inquisição; Justiça eclesiástica; Igreja; Brasil colonial